The drivers of regional growth in Russia A baseline model with applications - Blöchliger, Hansjörg (OECD Economics Department Working Papers, 2018)
Russia is a federation of more than 80 regions spanning across a huge territory. Natural resource endowment, inherited industrial specialization, remoteness and climate conditions contribute to large regional disparities. This paper presents an empirical framework model for assessing determinants of regional growth in Russia between 2004 and 2015 with an extension to include sub-national fiscal policies. Baseline results show convergence rates of regional GDP per capita in line with the 2% "iron law of convergence" between countries. Capital investment, and public investment in particular, is a stronger driver of regional growth than in most OECD countries. Natural-resource rich regions are growing faster, and oil price shocks have little economic impact in these regions, pointing at Russia's centralized tax and transfer system. Subnational current government expenditure is associated with lower growth and slower regional convergence, suggesting low sub-national spending efficiency. There is also weak evidence that sub-national investment yields higher returns than federal government investment. Transfers have mixed effects depending on their nature. Budget equalization grants tend to slow regional growth as they reduce incentives to improve spending efficiency. On the other hand earmarked matching grants tend to spur growth and convergence as they direct resources towards more productive spending